Oceanic phytoplankton are a potentially important source of benzenoids to the remote marine atmosphere - Manon Rocco (Nature Portfolio, 2021)
A group of aromatic hydrocarbons in the remote marine atmosphere, typically classified as anthropogenic pollutants, are attributable to local biogenic sources, according to shipborne observations and mesocosm experiments.